The Influence of Technology In Studying Japanese - F S Suwita; B Rizkia H (Peneliti.net, 2021)
This research is motivated by economic growth in Indonesia with the large number of foreign investors entering Indonesia, one of which is Japan. For that, mastering a foreign language will be very important. This study aims to determine the effect of technology and technology trends used in studying Japanese. The method used in this research is descriptive method with observation and interviews. Interviews were conducted on 24 student respondents at the Indonesian Computer University. This research shows that by using technology, namely software for learning Japanese in the form of a digital dictionary, the learning process becomes easier and faster. This can be seen from the 3 characteristics analyzed, namely the use of the digital dictionary, effectiveness, and the type of digital dictionary application used. Therefore, maximizing technology in learning Japanese is an efficient way to develop Japanese language skills. The use of digital dictionaries in learning Japanese can help in finding synonyms, use of proper language and writing procedures. Applications that make it easy to use are applications that provide various language options for users, especially the choice of using English.